The Role of Digital Literacy on Online Opportunity and Online Risk in Indonesian Youth - Amia Luthfia; Daru Wibowo; Maria A. Widyakusumastuti; Mia Angeline (Asian Journal for Public Opinion Research)
The Internet and digital devices have become an important part of life among the youth (age 17-24) of today. During the COVID-19 pandemic in Indonesia, Internet use in youth increased by 19.3%, with an average usage of 11.6 hours per day. Youths gain a lot of opportunities from the Internet, but, it also exposes them to various risks. Therefore, there is a need for measures to make the Internet a safe place for youth, in a balanced way that addresses opportunities alongside risks, through digital literacy. It is expected that through digital literacy, youths can take advantage of online opportunities, without being subjected to any dangers. This study aims to examine the relationship between the digital literacy, online opportunities, and online risks of young people, while at the same time examining the influence of digital literacy on those online risks and opportunities. This study employed the quantitative study approach (explanatory study). Cross-sectional surveys and structured questionnaires were used for data collection. The results showed that youth's (age 17-24) monthly expenses, age, and education levels were important factors for digital literacy and online opportunity; also the digital literacy variable plays an important role and affects online risk and opportunity positively. Digital literacy has a greater influence on online opportunities than it has on online risks. As youths spend more time online, they become more digitally literate, which can enable them to benefit more from new technology. Unfortunately, those with greater digital literacy cannot find a way to avoid risks while seeking opportunities.